1997
DOI: 10.1038/sj.onc.1201636
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk in signal transduction: Ras-dependent induction of cAMP-responsive transcriptional repressor ICER by nerve growth factor

Abstract: The CREM gene encodes both activators and repressors of cAMP-induced transcription. By virtue of an alternative, intronic promoter within the gene, the ICER (Inducible cAMP Early Repressor) isoform is generated. ICER acts as a dominant negative regulator and is cAMP-inducible in various neuroendocrine cells and tissues. ICER negatively autoregulates its own expression, and appears to participate in the molecular events governing oscillatory hormonal regulations. Here we report that ICER is inducible with nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…1-3). Only a few previous studies on ICER gene expression have analyzed both mRNA and protein expression (3,7,9). In most of these studies, a close correlation was observed between mRNA and protein expression except for forskolin-treated AtT20 cells (3) and, as shown in this study, in macrophages.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…1-3). Only a few previous studies on ICER gene expression have analyzed both mRNA and protein expression (3,7,9). In most of these studies, a close correlation was observed between mRNA and protein expression except for forskolin-treated AtT20 cells (3) and, as shown in this study, in macrophages.…”
Section: Discussionmentioning
confidence: 49%
“…However, such an expression profile correlates well with the kinetics of IFN-␥-inhibited genes, such as LPL (12), with maximum decreases seen between 12 and 24 h. Several extracellular mediators have been shown to increase the intracellular ICER levels, including NGF, thyroid-stimulating factor, follicle-stimulating hormone, glucagons, noradrenaline, gastrin, and cholecystokinin (7-10, 48, 51, 92). Although most of these factors act by increasing intracellular cAMP levels, the use of pharmacological agents has shown that the action of NGF and gastrin was not mediated through this route (9,10). Similarly, the use of a range of pharmacological agents showed that the IFN-␥-induced ICER expression was not affected by inhibitors of cyclic nucleotide-dependent protein kinase, MAP kinases, Ca 2ϩ /calmodulin-dependent protein kinase, protein kinase C, and JAK2 but required activation of CK2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the kinetics of stimulation are different because, as demonstrated by Monaco and Sassone-Corsi (1997), CREB phosphorylation returns to basal levels after 2 h of incubation with NGF, whereas we observe a more sustained stimulation that is still noticeable after 8 h of incubation with RA. Many actions of RA are mediated by binding of RAR-RXR heterodimers to DNA response elements.…”
Section: Discussionmentioning
confidence: 57%
“…The isoforms function either as transcriptional repressor or activator, depending on the presence or absence of the transactivating domains (Q1 and/or Q2) (13,15,16). The second promoter is responsible for the regulation of an inducible CREM, inducible cAMP earlyexpressed in the brain (17) and has been suggested to play a role in T cells (18,19). However, CREM ␣ is bigger than ICER protein (36 vs 16 kDa), possesses a kinase inducible domain, and is regulated by promoter 1.…”
mentioning
confidence: 99%